Analysis of Student Learning Outcomes According to The Implementation of Project Based Learning (PjBL) - Syamsul Wahid S (Universitas Muhammadiyah Enrekang, 2025)
This research aims to determine student learning outcomes in terms of the implementation of Project Based Learning (PjBL) in the Physics Department, Faculty of Mathematics and Natural Sciences, Makassar State University. The type of research is descriptive survey research to obtain quantitative data. The population in this research were all students in the Physics Department of the 2024/2025 class who are currently in the 2nd semester consisting of 4 classes with a total of 100 students. The total sample in this research was 49 people. The sampling technique in this research used purposive sampling. The variable in this research was student learning outcomes. The data obtained showed that the value of student learning outcomes in terms of the implementation of Project Based Learning (PjBL) in the Physics Department, Faculty of Mathematics and Natural Sciences, Makassar State University was mostly in the very high category with a percentage reaching 75.51%. The factor of the very high value of student learning outcomes is because PjBL encourages students to learn actively, solve problems, and produce real products, all of which contribute to deeper understanding and better learning outcomes.